2017
DOI: 10.1021/acs.orglett.7b00833
|View full text |Cite
|
Sign up to set email alerts
|

Hydropyridylation of Olefins by Intramolecular Minisci Reaction

Abstract: An unprecedented cheap, mild and easy methodology for an intramolecular Minisci reaction based on a hydrogen atom transfer (HAT) initiated hydrofunctionalization of olefins was developed. The method is suitable for the construction of unusual dihydropyrano-pyridine and 1,2,3,4-tetrahydronaphthiridine structures and, unlike most similar reactions, does not require exclusion of air from the reaction medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Additionally, methods to achieve carbon–carbon bond formation to alkenes by HAT have been developed (e.g., reductive coupling [2228], formal hydromethylation [29], cycloisomerization [8,3031], hydrooximation [32], hydroheteroarylation [28,3335], hydroarylation [3638], and cross-coupling [37]). Many of these transformations have found applications in synthesis [6,3947].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, methods to achieve carbon–carbon bond formation to alkenes by HAT have been developed (e.g., reductive coupling [2228], formal hydromethylation [29], cycloisomerization [8,3031], hydrooximation [32], hydroheteroarylation [28,3335], hydroarylation [3638], and cross-coupling [37]). Many of these transformations have found applications in synthesis [6,3947].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have also been made to extend HAT methodologies to C−C bond formation, both in an intra‐ and intermolecular fashion: Baran's group developed a general C−C coupling reaction, utilising electron‐deficient alkenes as capable radical acceptors (Scheme a)(i) . Hydropyridylation of alkenes by intramolecular Minisci reaction was recently demonstrated by Starr, which allows for the formation of structures such as dihydropyranopyridines (Scheme a)(ii). Furthermore, whilst conducting the work described in this paper, Bonjoch showed that ketones were able to undergo radical cyclisation to their tertiary alcohol counterparts (Scheme a)(iii) …”
Section: Methodsmentioning
confidence: 99%
“…Prabhu group [51] Starr jand Bordi [54] described fluent, reasonable and lowcost approach for the construction of dihydropyrano-pyridine and 1,2,3,4-tetrahydronaphthiridine compounds through intramolecular Minisci-type reaction. The proposed mechanism based on the generation of carbon radical cation of the alkene chain 117 on protonated pyridine promoted by Fe complex.…”
Section: Ncmentioning
confidence: 99%